Assessment of ordinary solid waste generation in the canton of Belén in the period 2005-2015 (UNED Research Journal, 2016)
Municipal solid waste management is a serious problem in most developing countries and local governments must have reliable information to make decisions. I analized total waste, recoverable waste and organic waste generation in Belén, Heredia, Costa Rica from 2005 through 2015. I found significant differences between the periods 2005-2010 and 2010-2015 (p
Keywords: municipal solid waste generation; Municipality of Belén; comprehensive management